335PPD-L1 profile of nasopharyngeal cancer patients in Indonesia. (24th November 2019) - Handoko, H; Gondhowiardjo, S A; Adham, M; Lisnawati, L; Tobing, D L; Kodrat, H; Haryoga, I M; Dwiyono, A G; Kristian, Y A; Mayang Permata, T B
Abstract: Background: Molecular and biological characterization of nasopharyngeal cancer (NPC) is scarce. Clinical trials of emerging treatment such as immunotherapy for NPC in endemic area is lacking. Currently the most extensively studied immune related molecule that potentially become the target for treatment is PD-1/PD-L1. PD-L1 profile of NPC patients in Indonesia has never been studied before. This study aimed to elucidate PD-L1 profile from NPC specimens in Indonesia. Methods: Nasopharyngeal biopsy specimen was taken for PD-L1 protein examination with enzyme-linked immunosorbent assay (ELISA) method. Tissue specimen was homogenized and then ELISA test was conducted using ABCAM AB214565 kit. All protocols from the manufacturer kit was followed. Total protein concentration from homogenized tissue specimen was obtained through Bradford protein assay method. Then, PD-L1 concentration per mg protein of tissue specimen was calculated. Results: Twenty-four nasopharyngeal biopsy specimens was obtained. The average age of all patients was 45 years old. Sixteen (66.67%) out of 24 specimens were confirmed histologically to be undifferentiated nasopharyngeal carcinoma. The rest, 8 other specimens have normal histology. Average PD-L1 concentration from NPC specimens was 2, 186.67 ± 1, 399.32 pg/mg protein (Range: 461.76 to 4, 805.85 pg/mg protein). Average PD-L1 concentration from non NPC specimens was 612.43 ± 314.04 pg/mg protein (Range: 326.87 to 1, 155.19 pg/mg protein). Conclusions: From this preliminary result, PD-L1 protein (both in tumor cells and in immune cells) from NPC specimens has been shown to be elevated compared to normal nasopharyngeal epithelium. This finding indicate that further work is warranted to test anti PD-L1 drug for NPC patients that has failed all the standard treatment. Furthermore, our upcoming work would be exploring relationship between PD-L1, EBV, and tumor microenvironment from our NPC specimens. Legal entity responsible for the study: The authors. Funding: University of Indonesia. Disclosure: All authors have declared no conflicts of interest.